Indeks Literasi Keuangan dan Inklusi Keuangan Perbankan Syariah di Provinsi Sulawesi Selatan - Yunus, Kurniati; Rini, Rini (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to analyze the effect of Islamic financial literacy on financial inclusion of Islamic banking in South Sulawesi Province and to see the level of Islamic financial literacy and financial inclusion of Islamic banking in the people of South Sulawesi Province and the effect of financial literacy on financial inclusion of Islamic banking. This research uses this research to measure the level of financial literacy and financial inclusion of Islamic banking as well as the effect of Islamic financial literacy on financial inclusion in Islamic banking in South Sulawesi Province. The data processing method uses simple analysis. The results of this study indicate that the Islamic financial literacy index is in the medium category and the Islamic banking financial inclusion in South Sulawesi Province is in the low category which indicates that the level of public understanding of Islamic finance already exists but access to Islamic banking is still lacking and financial literacy has an influence on financial inclusion. Islamic banking in communities in South Sulawesi Province.